ChemInform Abstract: A Neutron Diffraction Study and Mode Analysis of Compounds of the System La1‐xSrxFeO3‐xFx (x = 1, 0.8, 0.5, 0.2) and an Investigation of Their Magnetic Properties. Issue 49 (3rd December 2013) - Clemens, Oliver; Berry, Frank J.; Wright, Adrian J.; Knight, Kevin S.; Perez‐Mato, J. M.; Igartua, J. M.; Slater, Peter R.
Abstract La1‐xSrxFeO3‐xFx (x = 1, 0.8, 0.5, 0.2, 0) phases are prepared by solid state reaction of stoichiometric mixtures of La2O3, SrCO3, and Fe2O3 (1250 °C, 30 h) followed by fluorination with poly(vinylidenefluoride) at 400 °C for 24 h.